Anti Escherichia Coli Activity of Some Medicinal Plants of High Altitude of Nepal - Bhargava, Dipak; Saha, Abhilasha; Mondal, Keshab Chandra; Pandit, Bijaya Raj; Shidiki, Amrullah; Chaudhary, Navin Kumar; Gupta, Ravi Shankar; Jha, Awadhesh Kumar (Med Phoenix, 2017)
Background: Plants and plant-based medicaments are the basis of many of the modern pharmaceuticals we use today for our various ailments. The aim of the present study was to find out the bioactive chemical constituents such as flavonoids, alkaloids, tannins, saponins, carbohydrate and to find out the anti E. coli activity of the ethanolic extracts of traditionally used ten medicinal plants of Nepal at an altitude of 1500 ft from above the sea level. Methods: Ethanolic extracts of ten commonly used medicinal plants were analyzed phytochemically and evaluated for their significant antimicrobial activity against the clinical isolates of Escherichia coli. Mean zones of inhibition were calculated for each of the extracts. Results: The results revealed that though all the plants of the high altitude showed some degree of antimicrobial activity, the leaf extract of Syzygium cumini (5.7±0.3 cm), Chromolaena odorata (5.2±0.4 cm), Ocimum sanctum (4.7±0.6 cm) and Justicia adhatoda (3.2±0.3 cm) were most effective against the clinical isolates of E. coli, whereas the other six plant extracts were least effective against the clinical isolates of E. coli. Qualitative phytochemical analysis of the extracts revealed the presence of bioactive components. Seven of the plant extracts contain alkaloids, six of them contain glycosides, four of them contain flavonoids, three of them contain carbohydrate, oil and fats, two of them contain tannins, whereas only one of them contains saponins. Conclusion: The result of this study justified the folkloric usage of the studied plants and concluded that these plants extract have great potential in finding new clinically effective antimicrobial compounds. MED Phoenix Volume (1), Issue (1) July 2016, page: 3-9